The importance of formal education for the medication dispensing process: a cross-sectional study (Research, Society and Development, 2022)
Background: The dispensing of medications, if performed by professionals who do not have specific knowledge in relation to legislation, health problems, medications, and patient interaction, can result in damage to health. Objective:  This study aims to assess knowledge about medication dispensing by pharmacists and in the non-pharmaceutical workforce and to compare according to the different levels of formal education received. Methods: This is a cross-sectional study carried out in community pharmacies, and in educational institutions that offer the pharmacy technician course in Brazilian municipalities.  In employees of community pharmacies who worked directly with the dispensing of medication (pharmacists, pharmacy technicians, and clerks), and in students who will shortly graduate from the pharmacy technician, a questionnaire titled CDM-51 (Questionnaire for the Assessment of Knowledge about Drug Dispensing) was applied. Results: 146 employees answered the questionnaire, and 131 students completing the pharmacy technician course participated in the survey. This study showed that there is evidence that pharmacists had a higher score in the CDM-51 than the other participating professional categories. Conclusions: This research presents evidence on the importance of training to carry out the dispensing of medications, as in addition to highlighting the role of the pharmacist in this activity, it also promotes the training of professionals at a technical level to assist in the dispensing of medications, thus contributing to the improvement of services offered by community pharmacies.